2016
DOI: 10.3390/ijms17121988
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Structural Characterization, and Potential Antioxidant Activity of the Polysaccharides from Four Seaweeds

Abstract: Four seaweed polysaccharides were extracted from Sarcodia ceylonensis, Ulva lactuca L., Gracilaria lemaneiformis, and Durvillaea antarctica, respectively, by microwave-assisted extraction. The effect of three significant variables (extraction time, extraction temperature, and the ratio of water to raw material) on the process for extracting polysaccharides was investigated, along with the optimization of the extraction using the response surface method (RSM) with a Box–Behnken design. The polysaccharide struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 61 publications
(73 reference statements)
1
47
1
3
Order By: Relevance
“…The total carbohydrates content was 26.41% in the obtained ulvan. This result is higher than that obtained by He et al [24], and lower than Siddhanta et al [22], which was 23.71% and 47.4%, respectively. The obtained results for sulfate and carbohydrates are in the same trend of Jaulneau et al [25] who found that the ethanol-soluble ulvan had low quantities of sulfate and neutral sugars.…”
Section: Chemical Properties and Viscosity Of Ulvan Polysaccharidecontrasting
confidence: 75%
“…The total carbohydrates content was 26.41% in the obtained ulvan. This result is higher than that obtained by He et al [24], and lower than Siddhanta et al [22], which was 23.71% and 47.4%, respectively. The obtained results for sulfate and carbohydrates are in the same trend of Jaulneau et al [25] who found that the ethanol-soluble ulvan had low quantities of sulfate and neutral sugars.…”
Section: Chemical Properties and Viscosity Of Ulvan Polysaccharidecontrasting
confidence: 75%
“…Interestingly, compounds 37-39 and 48 were all isolated and characterized from the alga C. fragile and following this study, it was suggested that sterol compounds may prove to be useful biomarkers for this genus allowing for easier taxonomic distinction between other members of the Codiaceae family [44,45]. Much of the literature available for the genus Ulva involves biological activity studies on polysaccharides [46][47][48][49], many of the sterols found within this genus have shown promising in vitro bioactivity. In particular, the glycosidic sterol (47) from U. lactuca has been shown to be an effective anti-bacterial, anti-fungal and anti-inflammatory agent in vitro [41].…”
Section: Steroids/sterolsmentioning
confidence: 74%
“…Firstly, green algae produce a greater variety of sterolic compounds, and secondly, some structural differences are apparent. Green algal derived sterols appear to have a higher inclination towards glycosidic moieties along with long lipid esters that branch from the hydroxyl group on ring A of the steroid skeleton (38,47,48). Steroids derived from the brown algae appear to have no glycosidic attachments but display more diversity in the lipidic chains sprouting from the D ring (200-202).…”
Section: Steroids/sterolsmentioning
confidence: 99%
“…The IR spectra of DAP1, DAP2, DAP3, and DAP4 are shown in Figure 6. The absorption peak at 3,419-3,447 cm -1 is the stretch vibration of O-H (He, Xu, Chen, & Sun, 2016), but there is interference of the hydration peak. The weak peaks at 2,931-2,936 and 1,227-1,239 cm -1 are caused by the stretch vibration of C-H (Fan, Lin, Luo, Chun, & Luo, 2014).…”
Section: Fourier Transform Infrared (Ft-ir) Spectrometry Analysismentioning
confidence: 99%